Mating system, feeding type and ex situ conservation effort determine life expectancy in captive ruminants - Müller, Dennis W. H. (The Royal Society, 2011)
Zoo animal husbandry aims at constantly improving husbandry, reproductive success and ultimately animal welfare. Nevertheless, analyses to determine factors influencing husbandry of different species are rare. The relative life expectancy (rLE; life expectancy (LE) as proportion of longevity) describes husbandry success of captive populations. Correlating rLE with biological characteristics of different species, reasons for variation in rLE can be detected. We analysed data of 166 901 animals representing 78 ruminant species kept in 850 facilities. The rLE of females correlated with the percentage of grass in a species' natural diet, suggesting that needs of species adapted to grass can be more easily accommodated than the needs of those adapted to browse. Males of monogamous species demonstrate higher rLE than polygamous males, which matches observed differences of sexual bias in LE in free-living populations and thus supports the ecological theory that the mating system influences LE. The third interesting finding was that rLE was higher in species managed by international studbooks when compared with species not managed in this way. Our method facilitates the identification of biological characteristics of species that are relevant for their husbandry success, and they also support ecological theory. Translating these findings into feeding recommendations, our approach can help to improve animal husbandry.